2017
DOI: 10.1177/1065912917712478
|View full text |Cite
|
Sign up to set email alerts
|

Stealth Democracy Revisited: Reconsidering Preferences for Less Visible Government

Abstract: Understanding public preferences for governing processes is an understudied area of research. In this paper, I evaluate a set of critical assumptions relating to process preferences that the literature has thus far not addressed. I specifically address the claims made by John Hibbing and Elizabeth Theiss-Morse in their seminal book, Stealth Democracy, which suggests that people prefer political decisions to be made via expert-based governing arrangements to promote a level of efficiency and effectiveness withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…This performance/expectation gap was detected in government officials as well as the general public in case studies in the US and Australia [55]. These results overlap with other authors who have found sometimes contradictory preferences for participation in surveys that force dichotomous choices on participants between pure citizen or pure technocratic government control [50,[60][61][62]. Our interpretation is that such framing overly focuses on extremes of direct or representative democracy, which misses the partnership preferred by citizens in most mature democracies.…”
Section: Public Participation As a Way Of Building Political Trustsupporting
confidence: 69%
See 1 more Smart Citation
“…This performance/expectation gap was detected in government officials as well as the general public in case studies in the US and Australia [55]. These results overlap with other authors who have found sometimes contradictory preferences for participation in surveys that force dichotomous choices on participants between pure citizen or pure technocratic government control [50,[60][61][62]. Our interpretation is that such framing overly focuses on extremes of direct or representative democracy, which misses the partnership preferred by citizens in most mature democracies.…”
Section: Public Participation As a Way Of Building Political Trustsupporting
confidence: 69%
“…It has been contended that citizens are mostly disinterested or conflicted regarding participation, and only engage through fear of loss and corruption [40,48]. However, more recently the weight of evidence has shifted against this, with data being re-interpreted as frustration with the existing participation modes and general lack of political participation [49][50][51][52]. Further empirical work has confirmed the importance of participation for political trust [53], with civic engagement factors having twice higher effect on trust than government performance factors [11,20].…”
Section: Public Participation As a Way Of Building Political Trustmentioning
confidence: 99%
“…Stealth democrats want independent experts or successful businessmen to take the most important decisions and reject partisan politics. The prevalence of stealth democratic attitudes has been observed in various contexts: the US (Hibbing and Theiss-Morse, 2002;VanderMolen, 2017;Medvic, 2019), Finland (Bengtsson and Mattila, 2009), the Netherlands (Coffé and Michels, 2014), or the UK (Webb, 2013;Stoker and Hay, 2017).…”
Section: What Do Citizens Expect From Their Political System? Existinmentioning
confidence: 99%
“…If we transpose their scale to one that approximates a 6 rung Arnstein ladder from 'citizen control' to 'informing' , this preferred 'midpoint' is equivalent to that of 'partnership'. From similar vantage points, other studies have investigated citizens' preferences through comparisons between direct democracy, elected representatives and technocratic rule in various countries such as Finland [37], Denmark [38] America [14,39] and Spain [40]. The results were often indeterminant and contradictory with preferences that were contextual and seemed to straddle all three modes.…”
Section: The Disparity Between Participation Expectations and Experiementioning
confidence: 99%
“…This distaste was only balanced by the fear that by not being involved in politics would encourage corruption and advantage the political class, so people felt forced to be involved. Other researchers have critiqued this work from the normative perspective [12] and also methodologicallyas being limited by the interpretation of the focus group results [13] and the shallow and contextual preferences expressed [14]. Other empirical studies have focussed on assessing the existing attitudes of large population samples (such as electoral and telephone surveys) toward different types of participation.…”
Section: Introductionmentioning
confidence: 99%